2021
DOI: 10.1002/joc.7073
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal evaluation of gridded precipitation products for the high‐altitude Indus basin

Abstract: The high-altitude Indus basin is one of the most complex and inadequately explored mountain terrains in the World, where reliable observations of precipitation are highly lacking. Therefore, spatially distributed precipitation products developed at global/regional scale are often used in several scientific disciplines. However, large uncertainties in precipitation estimates of such precipitation data sets often lead to suboptimal outcomes. In this study, performance of 27 widely used gridded precipitation prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…In the several previous studies (Tables S1 and S2 in Supporting Information S1), the discrepancies in runoff composition can be largely explained by the varying magnitudes of precipitation inputs (e.g., ranging between 311 and 832 mm in the UI and 326-942 mm in the USD in annual means). Uncertainties resulting from the challenges/issues in precipitation inputs for model calibration and validation have been widely recognized and assessed in the TP region (Dahri et al, 2021;Lutz et al, 2014Lutz et al, , 2016Pellicciotti et al, 2012;Ragettli et al, 2013;Sun & Su, 2020;Wortmann et al, 2018). Therefore, developing a homogenized and representative climate data archive is urgently needed for a better understanding or assessment or quantification of current and future water availability in the TP.…”
Section: Uncertaintymentioning
confidence: 99%
“…In the several previous studies (Tables S1 and S2 in Supporting Information S1), the discrepancies in runoff composition can be largely explained by the varying magnitudes of precipitation inputs (e.g., ranging between 311 and 832 mm in the UI and 326-942 mm in the USD in annual means). Uncertainties resulting from the challenges/issues in precipitation inputs for model calibration and validation have been widely recognized and assessed in the TP region (Dahri et al, 2021;Lutz et al, 2014Lutz et al, , 2016Pellicciotti et al, 2012;Ragettli et al, 2013;Sun & Su, 2020;Wortmann et al, 2018). Therefore, developing a homogenized and representative climate data archive is urgently needed for a better understanding or assessment or quantification of current and future water availability in the TP.…”
Section: Uncertaintymentioning
confidence: 99%
“…compared the precipitation gradient characteristics obtained from ERA5 and gauge observations in the monsoon-dominated and westerlies-dominated HMA basins, suggesting that ERA precipitation can capture the pattern of precipitation gradient in most basins. Dahri et al (2021b) evaluated 27 gridded precipitation products in the high-altitude Indus, and suggested that among all the products, ERA5 exhibited the most acceptable performance for all sub-regions of the upper Indus. However, existing studies about ERA5 precipitation estimates are mostly focused on the spatiotemporal performances in the TP based on limited gauge observations which are mostly located in the eastern TP region.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, exchanging data between the four UIB member countries is complicated (Qamar et al., 2019; Salzmann et al., 2014). Efforts to overcome the paucity of direct observations in the UIB include using gridded observational datasets (from sources such as gauge and satellite measurements) and reanalysis, which have various levels of accuracy and also can give contradictory results (Dahri, Ludwig, Moors, & et al., 2021; H. Li et al., 2018; Palazzi et al., 2013). The questions below reflect attempts to improve data collection and monitoring across the UIB. …”
Section: Integrated Earth System Processesmentioning
confidence: 99%